The Eyes of Elephants: Changing Perceptions - Rothfels, Nigel (Tidsskrift for kulturforskning, 2008)
By placing two early twentieth-century images of elephants against a broader background of ideas about the animals, this essay critiques a particularly modern claim that by looking into the eye of an elephant one can gain a deeper understanding of the animal and its consciousness. In recent decades, elephant eyes have become ubiquitous markers in popular, natural historical, and rights-based studies of the animal; indeed, it has become difficult to open any book about elephants and not find at least one and sometimes many close-up shots of eyes. By examining this way of looking at elephants through placing it in a historical context, and by demonstrating how the animal’s eye has become central to a discourse of suffering connected to modern elephants, this essay calls for a re-examination of broadly held assumptions about the animal.